Stable Isotopes of Precipitation During Tropical Sumatra Squalls in Singapore - He, Shaoneng (2018)
Sumatra Squalls, organized bands of thunderstorms, are the dominant mesoscale convective systems during the intermonsoon and southwest monsoon seasons in Singapore. To understand how they affect precipitation isotopes, we monitored the δ value of precipitation daily and continuously (every second and integrated over 30 s) during all squalls in 2015. We found that precipitation δ18O values mainly exhibit a “V”‐shape pattern and less commonly a “W”‐shape pattern. Variation in δ18O values during a single event is about 1 to 6‰ with the lowest values mostly observed in the stratiform zone, which agrees with previous observations and modeling simulations. Reevaporation can significantly affect δ values, especially in the last stage of the stratiform zone. Daily precipitation is characterized by periodic negative shifts in δ value, largely associated with the squalls rather than moisture source change. The shifts can be more than 10‰, larger than intraevent variation. Initial δ18O values of events are highly variable, and those with the lowest values also have the lowest initial values. Therefore, past convective activities in the upwind area can significantly affect the δ18O, and convection at the sampling site has limited contribution to isotopic variability. A significant correlation between precipitation δ18O value and regional outgoing longwave radiation and rainfall in the Asian monsoon region and western Pacific suggests that regional organized convection probably drives stable isotopic compositions of precipitation. A drop in the frequency of the squalls in 2015 is related to weak organized convection in the region caused by El Niño.